POSSIBILITIES OF INCLUSION OF NEWCOMERS IN GENERAL SCHOOLS OF LATVIA - Danilāne, Liga; Danilāne, Lauma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
At the time when Russia is conducting military operations in Ukraine, Latvia provides all possible political, financial, military and humanitarian support to Ukraine, including hosting Ukrainian residents fleeing the war in Latvia. Education plays a vital role in the economic, social and cultural integration of migrants and refugees in the host country. Education is a key tool for transitioning from humanitarian to development and integrating those granted asylum into society.  The aim of study: to study the possibilities and threats of inclusion of newcomers in general education schools and to analyze the experience of students included in general education schools of the city of Rēzekne and Rēzekne district.